Current sustainability and electromigration of Pd, Sc and Y thin-films as potential interconnects - Yang, Yong; Xu, Shengyong; Xie, Sishen; Peng, Lian-Mao (Nano-Micro Letters, 2010)
The progress on novel interconnects for carbon nanotube (CNT)-based electronic circuit is by far behind the remarkable development of CNT-field effect transistors. The Cu interconnect material used in current integrated circuits seems not applicable for the novel interconnects, as it requires electrochemical deposition followed by chemical-mechanical polishing. We report our experimental results on the failure current density, resistivity, electromigration effect and failure mechanism of patterned stripes of Pd, Sc and Y thin-films, regarding them as the potential novel interconnects. The Pd stripes have a failure current density of (8∼10)×106 A/cm2 (MA/cm2), and they are stable when the working current density is as much as 90% of the failure current density. However, they show a resistivity around 210 μΩ·cm, which is 20 times of the bulk value and leaving room for improvement. Compared to Pd, the Sc stripes have a similar resistivity but smaller failure current density of 4∼5 MA/cm2. Y stripes seem not suitable for interconnects by showing even lower failure current density than that of Sc and evidence of oxidation. For comparison, Au stripes of the same dimensions show a failure current density of 30 MA/cm2 and a resistivity around 4 μΩ·cm, making them also a good material as novel interconnects.